Sunset, Brighton, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
Photo showing sunset at the Brighton Pier in La Brea, Trinidad.
Colour: Black and White ; Style: Landscape ; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Asphalt industry; Pitch Lake, The; Brighton Pier; Sun--Rising and setting